2000
DOI: 10.4098/at.arch.00-72
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences of four sympatric species of shrews

Abstract: Habitat preferences were studied in a shrew community of two semiaquatic species, Neomys anomalus Cabrera, 1907 and N. fodiens (Pennant, 1771), and two terrestrial species, Sorex araneus Linnaeus, 1758 and S. minutus Linnaeus, 1766, in a study area (5600 m ) alongside a small stream in Białowieża Forest (E Poland). Preferences were estimated by relating frequency of captures with macro-and microhabitat characteristics of trapping points. Distance to the stream and ground wetness appeared to be more important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
3
41
0
2
Order By: Relevance
“…The Eurasian pygmy shrew is more strongly associated with wet habitats than the common shrew (Rychlik 2000). Therefore, clear-cuts, which are generally drier than closed forest (Hansson 1992b), could be less suitable for S. minutus than for S. araneus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eurasian pygmy shrew is more strongly associated with wet habitats than the common shrew (Rychlik 2000). Therefore, clear-cuts, which are generally drier than closed forest (Hansson 1992b), could be less suitable for S. minutus than for S. araneus.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to assume that in the long term, the effects of disturbance on species abundance will taper off and finally disappear as was the case in North America (Zwolak 2009). Both analyzed species of shrews are considered habitat generalists (Churchfield et al 1997a), but the Eurasian pygmy shrew has wider niche breadth (Rychlik 2000) and is less dependent on habitat productivity than the common shrew (Hanski and Kaikusalo 1989;Churchfield et al 1997b). Therefore, lack of response of the Eurasian pygmy shrew to habitat change in both zones may be attributed to opportunistic traits of this species.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, N. anomalus rather avoids places with high wetland vegetation. Similar microhabitat preferences were displayed by this species in the Białowieża Forest (Rychlik 2000(Rychlik , 2001. Thus, as previously suggested by Rychlik & Pucek (1995), also on the basis of the present results it can be concluded that leaving unmown wet meadows and sedge swamps seems to be indispensable for maintenance of this species.…”
Section: Discussionmentioning
confidence: 57%
“…A similar trend in this species (and also in other shrews, e.g. Sorex araneus and S. minutus, and the root vole Microtus oeconomus) was observed by Rychlik (2000Rychlik ( , 2001, who suggested that roots of trees and the gaps between tussocks of sedges and the tree trunks provide the animals with good shelters and nesting dens.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation